2019
DOI: 10.3390/foods8100429
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Emulsions with Extracts of Cactus Pear Added in A Yogurt: Antioxidant Activity, In Vitro Simulated Digestion and Shelf Life

Abstract: Consumers demand so-called natural in which additive and antioxidant preservatives are from natural origin. Research focuses in using extracts from plants and fruits that are rich in bioactive compounds such as phenolics and betalains, but these are also prone to interact with proteins and are exposed to suffer degradation during storage. In this work, we developed a fortified yogurt with the addition of betalains and polyphenols from cactus pear extract encapsulated in a multiple emulsion (ME) (W1/O/W2). Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
2
24
1
Order By: Relevance
“…The representative band of the OH groups was found at 1037 cm −1 , which not only indicated the presence of the glycerol used as a plasticizer [64], but also the difference in intensity between each of the samples. This can be attributed to the presence of both phenolic compounds and betalains found in the xoconostle filtrate used as the aqueous phase of the nanoemulsion [19,20].…”
Section: Thermal Properties and Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
See 2 more Smart Citations
“…The representative band of the OH groups was found at 1037 cm −1 , which not only indicated the presence of the glycerol used as a plasticizer [64], but also the difference in intensity between each of the samples. This can be attributed to the presence of both phenolic compounds and betalains found in the xoconostle filtrate used as the aqueous phase of the nanoemulsion [19,20].…”
Section: Thermal Properties and Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…To quantify total betalains, the protocol established by [19] was followed, whereby 1 mL of sample was taken and mixed with 20 mL of 20% methanol (PQ06121, Fermont, Monterrey, Mexico). Absorbance readings were taken using a spectrophotometer (JENWAY, Model 6705, Dunmow, UK) at a wavelength of 483 nm (betaxanthines) and 538nm (betacyanins).…”
Section: Total Betalains Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This fruit is an excellent source of bioactive compounds, such as phenolic acids and flavonoids, among others, which could contribute to the prevention of chronic diseases, such as type 2 diabetes mellitus (Cenobio-Galindo, Díaz-Monroy, et al, 2019;Medina-Pérez et al, 2019). Unfortunately, bioactive compounds are sensitive to various conditions, such as the presence of oxygen, light, heat, among others, and thus it is necessary to incorporate them into a stable system to ensure their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Cenobio‐Galindo et al. (2019) have shown that bioactive compounds (total phenols, flavonoids, and betalains) from cactus pear extract, encapsulated in double emulsions, are adequate to prevent the loss of the antioxidant activity and increment the shelf life of yogurt. The bioactive compounds were protected in the gastric and intestinal digestion by the double emulsions.…”
Section: Introductionmentioning
confidence: 99%